Tipologi Pemikiran tentang Kewenangan Sunnah di Era Modern - Maizuddin M. Nur (Substantia: Jurnal Ilmu-Ilmu Ushuluddin, 2012)
The Islamic modern world, which was started since in the 19th century,  provided various religious thoughts. One of them was thought on sunnah authority. This discourse attracted many scholars from various fields, which  resulted to various perfectives on the discourse. Surely, the variety could be  analyzed and categorized into certain types based on categorization of logic. The  categorizing is viable because the various thought that were produced by modern- contemporer personages are not absolutely different from each other, where its  form and character still can be divided. At least there are four typologies regarded  to the thought on sunnah authority, they are: ideal totalistic, ideal restrictive, ideal generality and paradigmatic. These typologies are taken from various perfectives  and supported by various approaches in understanding sunnah authority and  hadith validation. These typologies also reflect modern personage‟s struggle in  understanding sunnah authority and hadith validation in human life